2005
DOI: 10.1901/jeab.2005.96-04
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience and Learning: Lessons From Studying the Involvement of a Region of Cerebellar Cortex in Eyeblink Classical Conditioning

Abstract: How the nervous system encodes learning and memory processes has interested researchers for 100 years. Over this span of time, a number of basic neuroscience methods has been developed to explore the relationship between learning and the brain, including brain lesion, stimulation, pharmacology, anatomy, imaging, and recording techniques. In this paper, we summarize how different research approaches can be employed to generate converging data that speak to how structures and systems in the brain are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…A recent study reported that Purkinje cells in cerebellar sulci exhibit some degree of multiple climbing fiber innervation, even in adult, wild-type mice, suggesting that some cerebellar regions may function well with multiple climbing fiber innervation (Nishiyama and Linden, 2004). Eyeblink conditioning, the OKR, and rotorod performance all depend on different regions of the cerebellum (Le Marec and Lalonde, 1997;Katoh et al, 1998;Gerwig et al, 2005;Villarreal and Steinmetz, 2005). Thus, a region-dependent effect of multiple climbing fiber innervation could differentially affect these tasks.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that Purkinje cells in cerebellar sulci exhibit some degree of multiple climbing fiber innervation, even in adult, wild-type mice, suggesting that some cerebellar regions may function well with multiple climbing fiber innervation (Nishiyama and Linden, 2004). Eyeblink conditioning, the OKR, and rotorod performance all depend on different regions of the cerebellum (Le Marec and Lalonde, 1997;Katoh et al, 1998;Gerwig et al, 2005;Villarreal and Steinmetz, 2005). Thus, a region-dependent effect of multiple climbing fiber innervation could differentially affect these tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that muscimol does not act on axons so the mossy fiber and climbing fiber projections to the cerebellar cortex are intact and fully functional, as is the cortex itself, yet no part or aspect of the memory trace develops in the cortex over the many days of training while the interpositus nucleus is inactivated. This extraordinary result has been repeated independently and exactly in three other laboratories using eyelid conditioning: David Lavond at the University of Southern California using reversible cooling of the interpositus in the rabbit (Clark et al, 1992; was actually the first such study published); Joseph Steinmetz then at the University of Indiana using muscimol in the interpositus of the rabbit (Villarreal and Steinmetz, 2005); and John Freeman at the University of Iowa using muscimol in the intepositus of the rat (Freeman et al, 2005). In all cases there was no savings in post-inactivation training.…”
mentioning
confidence: 78%
“…While the exact role of the cerebellar cortex in classical eyeblink conditioning remains an issue of debate (Attwell et al, 2002; Freeman and Steinmetz, 2011; Green and Steinmetz, 2005; Hong and Optican, 2008; Koekkoek et al, 2003; Kotani et al, 2006; Wang and Liu, 2011; Yamazaki and Nagao, 2012), one suggestion is that it aids in the establishment of IP plasticity and/or modulates topography of the behavioral response (Steinmetz and Lindquist, 2009; Villarreal and Steinmetz, 2005). Plasticity at the parallel fiber–Purkinje cell synapse occurs as a result of co-activation of the 2 primary sensory inputs to the cerebellum, mossy fibers from granule cells and climbing fibers from the dorsal accessory olive (Thompson and Steinmetz, 2009).…”
Section: Discussionmentioning
confidence: 99%